Equivalent matrix structure modelling and control of a three‐phase flying capacitor multilevel inverter. Issue 7 (1st July 2014) - Bouhali, Omar; Francois, Bruno; Rizoug, Nassim
Abstract : In this study, an equivalent matrix structure of three‐phase flying capacitor multilevel inverters (FCMIs) is developed. This structure is obtained by using a switching function for each voltage level. For one switching function, there is more than one combination of gate signal to produce each output voltages. Hence (3 n ) switching functions are defined for all switch combinations of the output voltage and their corresponding switch states. Therefore the modulation strategy of a three‐phase FCMI is obtained in two steps. Firstly, the direct space‐vector modulation of the matrix converter is used to compute the switching functions. The gates signals of the three‐phase FCMI can be calculated by inversing the modelling part. In this work, the direct space‐vector multilevel modulation based on the use of 2 n different three level functions called modulation functions is presented. Using this approach, the modulation strategy of a three‐phase FCMI is designed without using a Park transform. To validate the effectiveness of the equivalent matrix structure modelling and control, simulation results are given for nine‐level FCMI. Moreover, experimental results are given for a three‐level neutral point clamped (NPC) converter prototype laboratory.